Comparative Study of Characteristics of Dye Sensitized Solar Cells Fabricated Using Substrates Coated with Fluorine Doped Tin Oxide and Titanium - Maharjan, Arbin (Journal of the Institute of Engineering, 2020)
Dye-sensitized solar cells (DSSCs) have attracted many researchers because it has potential to supplement and compete with other solar cell technologies like Silicon (Si) and Cadmium Telluride (CdTe). The fabrication of DSSCs requires a photo electrode and a counter electrode of transparent and conducting nature. The commercial DSSCs uses electrodes of fluorine doped tin oxide (FTO) glass substrates. These electrodes are expensive and hence, possible alternative materials that are cheaper and that would provide better performance under similar environmental condition should be explored. In this paper, titanium (Ti)-coated glass substrates were prepared and then used to prepare electrodes for fabricating DSSCs. Similarly, DSSCs were fabricated using electrodes of conventional FTO-coated glass substrates. Performance characteristics like cell efficiency (η%), fill-factor (FF), short circuit current density (JSC) and open circuit voltage (VOC) of both fabricated DSSCs were obtained using their respective J-V characteristic curves under similar illumination of 100 mW/cm2 and with comparable transmittance under the visible transmission spectrum of 300-850 nm. The obtained results showed that DSSCs prepared using electrodes of FTO coated glass substrates have 1.557 times better cell efficiency and 2.172 times better fill factor than that of DSSCs fabricated using electrodes of Ti-coated glass substrates.